ALLOCATION OF MARITIME TASK FORCE PERSONNEL UNIFIL CONTINGEN BASED ON ANALYSIS WORK LOADS - Ahmadi Ahmadi; Okol Sri Suharyo; Arimbo Arimbo; Aab Abdul Wahab (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
The workload of an organization is related to the efficient and effective utilization of human resources so that it can realize the vision, mission and objectives of the organization. Various methods are used to optimize the number of personnel in an organization, so that each task can be completed effectively and efficiently. KRI Diponegoro-365 personnel as the TNI Maritime Task Force, the Garuda Contingent can not be separated from the problems regarding the lack of conformity to workload with the allocation of the number of available personnel. To overcome this, an analysis of workload measurement is needed which can then be used for determine the allocation of the right number of personnel needed in each division. This study uses the measurement of NASA-TLX mental workload and physical workload according to TNI Roles. Both of these methods are then compared between mental and physical burden that occurs. From the results of the comparison, it was found that physical workload is needed in the completion of tasks in each division. After a comparison, then the determination of the allocation of the number of personnel will be carried out using the physical workload approach based on the description of the tasks in each division. The results of the calculation will then show the division that has excess or lack of personnel. The overall results obtained from this study can be concluded that the number of maritime task force personnel using the Diponegoro class KRI is appropriate, but the allocation of personnel in each division needs to adjust to the existing workload. Keywords: Workload, NASA-TLX (Task Load Index), Number of Military Personnel